Lado B Gallery: one year of history from creation to its outcomes (Palíndromo, 2025)
This article presents an experience report on the creation, organization, and maintenance of the Galeria Lado B, a visual arts exhibition space at the Federal Institute of Santa Catarina (IFSC), São Miguel do Oeste campus, during its first year of operation (2023/2024). The initiative emerged in response to the regional scarcity of permanent spaces for visual and fine arts exhibitions, which restricts community access and reduces educational opportunities. The aim is to analyze the administrative and curatorial strategies adopted and to discuss their impact on democratizing access to the visual arts within an academic context. The methodology combines an experience report, case study, and analysis of documentary and photographic records, encompassing both quantitative and qualitative data. Among the highlights, results include seven exhibitions, the voluntary participation of 22 artists, 3,337 visitors, 42 guided tours, and 30 educational activities, all of which strengthen ties between the institution, artists, and the community. It is concluded that, despite challenges such as transportation limitations and workload demands, the Galeria Lado B has established itself as a relevant space for valuing local and regional art, for cultural formation, and for reflections on educational curatorial practices.
Keywords: school art gallery; school exhibition spaces; visual arts education